Government environmental information disclosure and digital transformation of manufacturing companies: evidence from China - Xu, Songtao; Chen, Xia (Frontiers in Environmental Science, 2025)
Environmental pollution is a significant constraint on the sustainable development of manufacturing companies, while digital transformation has been proven to be an effective method for companies’ environmental governance. Government environmental information disclosure (GEID), as a crucial information governance tool, enhances the collaborative environmental governance capabilities of both government and external stakeholders of companies. Logically, this indicates that by emphasizing environmental regulation, GEID can promote corporate digital transformation. This study empirically analyzes the impact of GEID on the digital transformation of companies, using a sample of Chinese A-share listed manufacturing companies. The results indicate that higher local GEID levels significantly boost the digital transformation of manufacturing companies in the region, with a one-point increase in GEID resulting in a 0.31% rise in the degree of digital transformation. This conclusion remains robust across various endogeneity and robustness tests. Further analysis reveals that GEID primarily promotes digital transformation through mechanisms such as fostering companies’ green development strategies and green innovation, increasing R&D expenditure, and reducing financing constraints. Additionally, the study finds that the impact of GEID on digital transformation is especially significant in firms with poor environmental performance, low fixed asset ratios, non-state-owned enterprises, and during the post-2015 period. Despite heavy assets typically being seen as a barrier to digital transformation in heavily polluting industries, GEID still significantly promotes the digital transformation of asset-intensive enterprises. This study not only provides a new perspective on understanding the impact of GEID on corporate digital transformation but also offers empirical evidence for policymakers and corporate managers, thereby aiding enterprises in achieving sustainable development goals.